2020
DOI: 10.1002/pen.25485
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and experimental studies on the effect of thickness difference between up and down gas layers on sheet polymer gas‐assisted extrusion forming

Abstract: In this study, to make gas-assisted extrusion (GAE) can be better applied to conventional horizontal extrusion forming process, the thickness difference between up and down gas layer was simulated for the first time by GAE of molten high-density polyethylene sheet. In order to ascertain the effects of the thickness difference of up and down gas layers on sheet extrusion molding, a method based on the model of two-phase (gas and melt) flow was put forward, and an outer-layer GAE isothermal numerical simulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The manufacturing technology based on gas-assisted extrusion (GAE) forming is mostly used for the processing and manufacturing of round tubes, square tubes, and irregular shapes, which has the advantages of high production efficiency and relatively simple secondary processing procedures. In this study, the GAE method is intended to be used to manufacture the flexible robot body. The evolution of GAE forming technology dates back to the 1960s when it was predominantly used for extruding polyethylene foam plastics.…”
Section: Introductionmentioning
confidence: 99%
“…The manufacturing technology based on gas-assisted extrusion (GAE) forming is mostly used for the processing and manufacturing of round tubes, square tubes, and irregular shapes, which has the advantages of high production efficiency and relatively simple secondary processing procedures. In this study, the GAE method is intended to be used to manufacture the flexible robot body. The evolution of GAE forming technology dates back to the 1960s when it was predominantly used for extruding polyethylene foam plastics.…”
Section: Introductionmentioning
confidence: 99%
“…This study was based on previous research on the vertical direction of horizontal extrusion, and an improved GAE forming process was investigated using different up and down gas layer thicknesses. [30,31] It can provide a practical and theoretical basis for the GAE of daily profiles, aimed at improving the quality and efficiency of plastic extrusion products.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the good performance of the improved die, when the polymer is extruded horizontally, the melt in the molten state clogs the die and is difficult to clean. Jiang et al [59] proposed, for the first time, the use of different up and down gas layer thicknesses, and studied the effect of different thicknesses on sheet extrusion. Finally, it was suggested that the thickness of the underlying layer can be increased appropriately during actual extrusion to prevent the sheet from falling at the exit.…”
Section: Introductionmentioning
confidence: 99%